Tata Kelola Penyelenggaraan Pemerintahan Negeri Batu Merah Kecamatan Sirimau Kota Ambon - Rukoyah Rukoyah; Muhtar Muhtar (INDO PUBLISHING, 2026)
This study aims to analyze the governance of the Batu Merah Village Government, Sirimau District, Ambon City, in the implementation of Law Number 6 of 2014 concerning Villages. The research focuses on the implementation of good governance principles, namely supervision, responsiveness, transparency, and community participation in village governance administration. This study employed a qualitative descriptive research method with data collection techniques through observation, interviews, and documentation. Informants in this study consisted of village government officials, the Village Consultative Body (BPD), community leaders, and local residents. The results of the study indicate that the implementation of Law Number 6 of 2014 in Batu Merah Village has generally been carried out adequately, particularly in community involvement in development planning and village governance. However, several obstacles remain, such as the lack of transparency in village budget management, the absence of clear standard operating procedures in the recruitment of village officials, and delays in village head elections. In addition, coordination among village institutions still requires improvement to realize effective and accountable governance. Therefore, strengthening institutional capacity, increasing public participation, and improving transparency are necessary to support the realization of good governance in Batu Merah Village.